2024
DOI: 10.1186/s13046-024-02983-3
|View full text |Cite
|
Sign up to set email alerts
|

ThermomiR-377-3p-induced suppression of Cirbp expression is required for effective elimination of cancer cells and cancer stem-like cells by hyperthermia

Tao-Yan Lin,
Jun-Shuang Jia,
Wei-Ren Luo
et al.

Abstract: Background In recent years, the development of adjunctive therapeutic hyperthermia for cancer therapy has received considerable attention. However, the mechanisms underlying hyperthermia resistance are still poorly understood. In this study, we investigated the roles of cold‑inducible RNA binding protein (Cirbp) in regulating hyperthermia resistance and underlying mechanisms in nasopharyngeal carcinoma (NPC). Methods CCK-8 assay, colony formation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 138 publications
(359 reference statements)
0
2
0
Order By: Relevance
“…It is one of the key mechanisms for NPC cells to resist anti-tumor measures, leading to metastasis and invasion ( 59 ). Multiple studies have confirmed that TGF-β ( 60 ), NF-κB ( 61 ), Wnt ( 62 ), Akt ( 63 ), Notch ( 64 ), and other signaling pathways are involved in EMT in NPC, while EBV infection ( 65 ), abnormal gene expression ( 66 ), hypoxia ( 67 ), and abnormal expression of non-coding RNA ( 68 ) are involved in regulating these signaling pathways. Stanniocalcin-2 promotes cell EMT by activating the ITGB2/FAK/SOX6 signaling pathway in NPC ( 69 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is one of the key mechanisms for NPC cells to resist anti-tumor measures, leading to metastasis and invasion ( 59 ). Multiple studies have confirmed that TGF-β ( 60 ), NF-κB ( 61 ), Wnt ( 62 ), Akt ( 63 ), Notch ( 64 ), and other signaling pathways are involved in EMT in NPC, while EBV infection ( 65 ), abnormal gene expression ( 66 ), hypoxia ( 67 ), and abnormal expression of non-coding RNA ( 68 ) are involved in regulating these signaling pathways. Stanniocalcin-2 promotes cell EMT by activating the ITGB2/FAK/SOX6 signaling pathway in NPC ( 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of drug resistance, tumor repopulating cells (TRCs) with stem cell-like cancer cell characteristics resist chemotherapy and radiotherapy by reducing the sensitivity to iron death ( 114 ). Based on such an ecological theory, researchers can consider using ecological therapies to combat NPC (by altering the surrounding environment to eliminate specific targets), such as destroying tumor habitats through hyperthermia ( 68 ) and reducing drug resistance in NPC cells through adaptive therapies ( 115 ). Therefore, it is helpful for researchers to develop more effective anti-cancer strategies to examine NPC in a new system.…”
Section: Discussionmentioning
confidence: 99%